2012
DOI: 10.1097/ccm.0b013e31824519ce
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcome after moderate and severe traumatic brain injury

Abstract: Objective The International Mission on Prognosis and Analysis of Clinical Trials (IMPACT) and Corticoid Randomisation After Significant Head injury (CRASH) prognostic models predict outcome after traumatic brain injury (TBI) but have not been compared in large datasets. The objective of this is study is to validate externally and compare the IMPACT and CRASH prognostic models for prediction of outcome after moderate or severe TBI. Design External validation study. Patients We considered 5 new datasets with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
1
14

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(128 citation statements)
references
References 25 publications
8
105
1
14
Order By: Relevance
“…We propose that the ANN model with 96.13 % AUC is optimal for predicting 6-month functional outcome and the NB with 90.14 % AUC is the best algorithm for predicting 6-month mortality. Several studies have evaluated the ability of prediction models to correctly predict outcomes for patients with TBI and showed a wide range of AUCs (65 to 85 %) [17,18,22]. We found that our data mining models (ANN, NB, DT) accurately discriminated functional outcome with an AUC of 92-96 % and mortality with an AUC of 78-91 %, which compared favorably with AUCs reported in previous studies.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We propose that the ANN model with 96.13 % AUC is optimal for predicting 6-month functional outcome and the NB with 90.14 % AUC is the best algorithm for predicting 6-month mortality. Several studies have evaluated the ability of prediction models to correctly predict outcomes for patients with TBI and showed a wide range of AUCs (65 to 85 %) [17,18,22]. We found that our data mining models (ANN, NB, DT) accurately discriminated functional outcome with an AUC of 92-96 % and mortality with an AUC of 78-91 %, which compared favorably with AUCs reported in previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…The results from the analysis of important attributes (Table 5) indicate that the GCS scores at different time points (ER, 7th, and 14th day), GCS changes between time points (from ER to 7th day and from ER to 14th day), and age were the most influential variables in the performance of our prediction models. As the data were collected in a tertiary trauma center in an agricultural county where persons 65 years or older represent more than 14 % of the population and motorcycle is the dominant method of transportation, the mean age of these patients with head injury, 55.5 years, is older than in most previous studies of adults with TBI [9,18,[61][62][63]. Pupillary size was shown to be a non-significant predictor in our study.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…This involves dividing the study population into subgroups according to the early severity of their injury. This is done by taking into account factors such as clinical and imaging findings and patient age 57 . The point of dichotomization is adjusted according to the subgroup.…”
Section: [H1] Criticismsmentioning
confidence: 99%
“…La TAC rappresenta uno strumento di grande utilità per stabilire l' evoluzione e la prognosi del paziente con TBI, anche se non è stata stabilita una relazione statisticamente significativa [45]. Dai dati ottenuti dai referti dei pazienti dello studio CRASH è stato evidenziato che la compressione delle cisterne perimesencefaliche e la presenza di emorragia subaracnoidea traumatica si associa a prognosi negativa [50]. La proteina S100β presente nelle cellule gliali e e di Schwann è elevato nel sangue e nel liquor in risposta al danno.…”
Section: Prognosiunclassified